Are there Psychopaths in White-Collar Jobs?. Issue 8 (3rd August 2021) - Leeper Piquero, Nicole; Piquero, Alex R.; Narvey, Chelsey; Boutwell, Brian; Farrington, David P.
ABSTRACT: Psychopathy has been an important topic of study in psychology and increasingly in criminology. The adverse, antisocial behavior of psychopaths has been studied for quite some time, yet there remains less work on how psychopaths may (or may not) succeed in other life domains, including in particular employment. On this score, the literature provides competing hypotheses with respect to whether psychopaths will excel in the workplace – especially in high-level managerial positions. This paper uses data from the Cambridge Study in Delinquent Development to examine how psychopathy is related to white-collar employment, how the interaction of psychopathy and white-collar jobs is related to life success of failure in late middle adulthood, and the extent to which groups that were formed from combinations of psychopathy and white-collar employment differed as children on individual and environmental risk factors. Results provide support for the more classic view of psychopathy, since psychopaths are unlikely to be in managerial positions, evince worse childhood risk, and incur a significant amount of adult life failure.